Stable Transcriptional Repression and Parasitism of HIV-1 - Surya Shrivastava; Paige Charlins; Amanda Ackley; Heather Embree; Boro Dropulic; Ramesh Akkina; Marc S. Weinberg; Kevin V. Morris (Elsevier, 2018)
Gene-based therapies represent a promising treatment for HIV-1 infection, as they offer the potential for sustained viral inhibition and reduced treatment interventions. One approach developed here involves using conditionally replicating vectors (CR-vectors). CR-vectors utilize HIV-expressed proteins to replicate and disseminate along with HIV into the budding viral particles, thereby co-infecting target cellular reservoirs. We generated and characterized several CR-vectors carrying various therapeutic payloads of non-coding RNAs targeted to HIV-1, both transcriptionally and post-transcriptionally. Both virus and vector expression was followed in cell culture systems and T cells in the presence and absence of mycophenolic acid (MPA) selection. We find here that CR-vectors functionally suppress HIV expression in a long-term stable manner and that transcriptional targeting of and epigenetic silencing of HIV can be passaged to newly infected cells by the action of the CR-vector, ultimately establishing a sustained parasitism of HIV. Our findings suggest that CR-vectors with modulatory non-coding RNAs may be a viable approach to achieving long-term sustained suppression of HIV-1, leading ultimately to a functional cure. Keywords: non-coding RNA, HIV-1, conditionally replicating lentiviral vectors, epigenetic silencing, transcription